Fluorescence Immunohistochemistry by Confocal Laser-Scanning Microscopy for Studies of Semi-Ultrathin Specimens of Epoxy Resin-Embedded Samples - Iwasaki, Shin-ichi; Aoyagi, Hidekazu (IntechOpen, 2011)
None